Cold urticaria: A clue to a silent systemic disease - Joana Rodrigues Sarmento Branco; Sara Completo Marques; Piedade Sande Lemos; Anna Sokolova (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
A previously healthy 2-year-old boy with a history of recurrent hives after exposure to cold air. A diagnosis of cold-induced urticaria was confirmed by a positive ice cube test but in the investigation, we found hepatic cytolysis and a lack of alpha-1-protein band level in protein electrophoresis. Deficiency of alpha-1-protein was confirmed which prompted genotype sequencing and genetic studies, unveiling the ZZ genotype and Glu342Lys mutation of SERPINA1 gene respectively. Alpha1-antitrypsin deficiency (AATD) was identified in association with acquired cold urticaria.   In the last decades cases of AATD associated with cold urticaria have been described mostly in patients with Z allele. AATD results in inadequate inactivation of plasmatic proteases and, consequently, incomplete control of the inflammatory reaction, eventually predisposing to urticaria.   The authors suggest that AATD screening could be more frequently performed in the investigation of cold urticaria, since early AATD diagnosis is essential.